2015
DOI: 10.1111/eip.12271
|View full text |Cite
|
Sign up to set email alerts
|

Treatment effect with paliperidone palmitate compared with oral antipsychotics in patients with recent‐onset versus more chronic schizophrenia and a history of criminal justice system involvement

Abstract: AimLong‐acting injectable antipsychotics (APs) are not well studied in recent‐onset schizophrenia. This exploratory analysis of a study designed to reflect real‐world schizophrenia, as defined by patients, interventions and outcomes, compared relative treatment effect between once‐monthly paliperidone palmitate (PP) and daily oral APs in patients with recent‐onset or chronic illnessMethodsThis randomized, open‐label, event monitoring board–blinded study compared treatment response in subjects with schizophreni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 39 publications
(65 reference statements)
4
27
1
Order By: Relevance
“…Taken together, these results support the potential value of early intervention with PP1M and are consistent with previous reports (Heres et al, 2014; Kane et al, 2015; Llorca et al, 2013; Subotnik et al, 2015) that patients early in their psychiatric illness are often more responsive to treatment. Furthermore, they add to the growing body of evidence on the effects of PP1M in recently diagnosed schizophrenia patients (Bossie et al, 2011; Fu et al, 2014; Sliwa et al, 2012; Stevens et al, 2016; Zhang et al, 2015), including prospective parallel-group comparisons showing benefits with PP1M compared with daily oral antipsychotic treatment (Alphs et al, 2015; Schreiner et al, 2015). In these patients, the tolerability of PP1M's initiation dosing was similar to oral risperidone (Gopal et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these results support the potential value of early intervention with PP1M and are consistent with previous reports (Heres et al, 2014; Kane et al, 2015; Llorca et al, 2013; Subotnik et al, 2015) that patients early in their psychiatric illness are often more responsive to treatment. Furthermore, they add to the growing body of evidence on the effects of PP1M in recently diagnosed schizophrenia patients (Bossie et al, 2011; Fu et al, 2014; Sliwa et al, 2012; Stevens et al, 2016; Zhang et al, 2015), including prospective parallel-group comparisons showing benefits with PP1M compared with daily oral antipsychotic treatment (Alphs et al, 2015; Schreiner et al, 2015). In these patients, the tolerability of PP1M's initiation dosing was similar to oral risperidone (Gopal et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The results of a multicentre, double-blind (DB), randomized, placebo-controlled study showed that PP3M significantly delayed time to relapse compared with placebo in patients adequately treated with PP1M (Berwaerts et al, 2015). Several studies have reported on the feasibility and benefit of LAIs for the treatment of patients with early illness schizophrenia (Alphs, Bossie, Mao, Lee, & Starr, 2015;Schreiner et al, 2015;Subotnik et al, 2015;Weiden et al, 2009), but the effects of PP3M on early illness have not been investigated. This post hoc analysis examines the efficacy and safety of PP3M in a subpopulation of patients diagnosed with schizophrenia ≤5 years before trial enrolment.…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta‐analysis of randomized controlled trials with oral and long‐acting injectable atypical antipsychotics(risperidone and paliperidone) found that long‐acting injectable antipsychotics were associated with increased anxiety when compared with oral dosing of either atypical antipsychotic investigated (Misawa, Kishimoto, Hagi, Kane, & Correll, ). Increased anxiety has been reported in 10.6% of individuals receiving injectable paliperidone (Alphs, Benson, et al, ), and a comparative study with oral paliperidone found that injectable paliperidone was associated with an increase in anxiety (12%) significantly more frequently than was oral paliperidone (6%; Alphs, Bossie, Mao, Lee, & Starr, ).…”
Section: Pharmacological Treatment Of Anxiety In Schizophreniamentioning
confidence: 98%